Mild Biliary Pancreatitis: Diagnostic-Therapeutic Dilemma Continues - Lapolla, Francesco; Forlano, Immacolata; Fersini, Alberto; Tartaglia, Nicola; Ambrosi, Antonio; Neri, Vincenzo (JOP. Journal of the Pancreas, 2012)
Context Among the patients with mild acute biliary pancreatitis (ABP), without an increase of cholestasis indexes neither dilation of the intra-extra-hepatic biliary ducts, literature data show a variable range (45-75%) of common bile duct (CBD) stones carriers. It is useful to know if obstacles are present in the CBD. Objective To verify the sensibility of MRCP to determine the conditions of the CBD before the cholecystectomy. Methods Thirty-five patients with mild ABP (Glasgow score = 1) were studied in the period from January 2007 to February 2012; the diagnosis of ABP was made on the basis of the clinical symptoms, the laboratory data and the US instrumental data for the confirmation of the biliary etiology. All patients were submitted to an MRCP. Results MRCP was diagnostic for choledocholithiasis in 10 patients (28.6%) that were submitted to an ERCP/ES with radiologic and endoscopic confirmation of the presence of stones/sludge in the CBD with a complete clearance. During the same hospital stay, all the patients were submitted to cholecystectomy and no patients had a relapse of the acute pancreatitis. Conclusion MRCP seems to be the gold standard technique to be utilized in all patients with mild ABP avoiding ERCP/ES in patients without predictive factors of choledocholithiasis.